The Effect of Corona Anxiety and Death Anxiety on Maternal-Child Conflict in Home Quarantine related to :COVID-19 - Sahar Ehsani; Abbas Shahverdi; Manijeh Firouzi; Fatemeh Soltani (مطالعات اجتماعی روان‌شناختی زنان, 2023)
COVID-19 has changed the lifestyles and patterns of interaction in families. This study aimed to investigate the effect of coronavirus anxiety and death anxiety on the conflict between mothers and children aged 7 to 12 years in the home quarantine due to COVID-19. Thus, 160 mothers and primary school children in Tehran were studied. The results showed that increasing coronavirus anxiety in mothers increases conflict in children, which was represented in their paintings. The psychological symptoms of coronavirus anxiety were related to the position of the child, mother, and father on the child's drawing, and the physical symptoms of coronavirus anxiety disorder were related to the position of the child, mother, and father in the paintings. Also, death anxiety was related to the child's distance from the mother, the child's and the father's position. Furthermore, the mediating role of death anxiety on the relationship between coronavirus anxiety and Mother-Child Conflict was confirmed. Findings of the study were discussed with Parncutt's “Reflective Consciousness Theory” of maternal hypersensitivity at the time of arousal of fundamental anxiety.